Case mix and workload of patients seen at three private emergency centres in Cape Town, South Africa - Moolla, Zuraida (Division of Emergency Medicine, 2017)
Objectives: To determine the case mix and workload of patients presenting to three private emergency centres in Cape Town Design: A Prospective cross sectional observational study was undertaken Setting and subjects: A convenience sample of all prospective patients that presented to three private emergency centres namely Melomed Gatesville, Melomed Bellville and Melomed Mitchell's plain during the month of September 2013 The outcome measures included the following:- ● Determining basic metrics across all three units over study time ● Determining the triage parameters for patients sampled across three units ● Direct time study of patients through unit ● Determining Doctor to patient workloads ● Determining Nurse to patient workloads ● Determining average number of patients receiving special investigations Results: Third party funding was responsible for 91 % of patients seen. The patient profiles consisted primarily of lower acuity presentations. There were clear peaks of attendance with lower acuity presentations decreasing after 10 pm. The majority of patients were discharged and very few required specialist follow up. Conclusions: This study provides valuable information with regards to private emergency centres in the predominantly low income and low socio economic sectors of the Western Cape, Cape town thus allowing a greater focus on the operational aspects of Emergency Centres In these areas and to assist with future planning of the management and running of similar Emergency Centres.